Imaging the fate of implanted bone marrow stromal cells labeled with superparamagnetic nanoparticles - Jendelová, Pavla; Herynek, Vít; DeCroos, Jane; Glogarová, Katerina; Andersson, Benita; Hájek, Milan; Syková, Eva (Magnetic resonance in medicine, 2003)
Bone marrow stromal cells (MSCs) are pluripotent progenitor cells that have the capacity to migrate toward lesions and induce or facilitate site-dependent differentiation in response to environmental signals. In animals with a cortical photochemical lesion, the fate of rat MSCs colabeled with magnetic iron-oxide nanoparticles (Endorem) and bromodeoxyuridine (BrdU) was studied. MSCs were either grafted intracerebrally into the contralateral hemisphere of adult rat brain or injected intravenously. In vivo MRI was used to track their fate; Prussian blue staining and transmission electron microscopy (TEM) confirmed the presence of iron-oxide nanoparticles inside the cells. During the first week posttransplantation, the transplanted cells migrated to the lesion site and populated the border zone of the damaged cortical tissue. The implanted cells were visible on MR images as a hypointense area at the injection site and in the lesion. The hypointense signal persisted for more than 50 days. The presence of BrdU-positive and iron-containing cells was confirmed by subsequent histological staining. Three to 4 weeks after injection, <3% of MSCs around the lesion expressed the neuronal marker NeuN. Our study demonstrates that a commercially available contrast agent can be used as a marker for the long-term noninvasive MR tracking of implanted cells.
Keywords: Male; oxidy; Rats, Wistar; Dextrans; magnetická rezonanční tomografie; kontrastní látky; Brain; Bromodeoxyuridine; železo; buňky kostní dřeně; Bone Marrow Transplantation; Oxides; bromodeoxyuridin; mužské pohlaví; Suspensions; potkani Wistar; Magnetite Nanoparticles; transplantace kostní dřeně; Cell Movement; krysa rodu Rattus; magnetické nanočástice; Animals; suspenze; Iron; Contrast Media; Microscopy, Electron, Scanning; zvířata; Rats; pohyb buněk; dextrany; mozek; Ferrosoferric Oxide; Magnetic Resonance Imaging; oxid železnato-železitý; mikroskopie elektronová rastrovací; Bone Marrow Cells